DEVELOPMENT OF AN ECOLOGICAL, RISK‐BASED DECISION FRAMEWORK FOR RELEASING AND MANAGING WILD TURKEYS IN ONTARIO - Karen Bellamy; J. Bruce Pollard (Wildlife Society Bulletin)
Abstract: Ontario initiated wild turkey (Meleagris gallopavo silvestris) restoration efforts in 1984 and within 20 years had restored or established populations across much of southeastern and southwestern portions of the province. Within these areas, it is believed that expansion of agricultural and changing land use has extended suitable range into landscapes well beyond known historic range. There was interest in establishing wild turkey into other areas; however, expansion of turkey populations was not viewed by all groups as either desirable or appropriate. Through knowledge gained from assessment of habitat suitability, overlaying habitat information on historic distribution, factoring in land‐use change, and by considering prevailing weather patterns, we developed a terrestrial ecozone framework to define the spatial extent for turkey range expansion. At present, we consider the Mixedwood Plain Ecozone to represent a biologically suitable and ecologically appropriate framework for wild turkey expansion in Ontario. Using the Mixedwood Plain Ecozone boundary, a simple risk‐based decision tree was developed to deal with ecological, social, and economic risks of releasing turkeys at new locations in Ontario.